1997
DOI: 10.3354/meps161023
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differences in recruitment and population structure of a temperate reef fish

Abstract: The purpose of this study. was to assess the importance of pre-and post-settlement processes in the temperate reef fish Tautogolabrus adspersus at multiple spatial scales and in 2 distinct regions, Newfoundland, Canada, and the Gulf of Maine, USA. We examined a total of 20 sites (separated by 100 to 1000 m) nested within 10 locations (separated by ca 10 km). Greater numbers of adult fish were observed in Newfoundland than in the Gulf of Maine; however, higher abundances of newly recruited fish occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Similarly, Caselle & Warner (1996) demonstrated a correlation between microhabitat attributes and recruitment of Thalassoma bifasciatum that was not evident among sites around St Croix, US Virgin Islands. On temperate reefs, Levin (1991Levin ( , 1993 showed that the wrasse Tautogolabrus adspersus selected microhabitats with high coverage of filamentous algae at settlement, but among-reef variability in filamentous algae did not predict large-scale patterns of recruitment (Levin et al 1997). The inability to scale-up may occur because of low variability of the preferred substratum (Tolimieri 1995) or because the habitat signal may be scale-dependent (Syms 1995, Syms & Jones 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Caselle & Warner (1996) demonstrated a correlation between microhabitat attributes and recruitment of Thalassoma bifasciatum that was not evident among sites around St Croix, US Virgin Islands. On temperate reefs, Levin (1991Levin ( , 1993 showed that the wrasse Tautogolabrus adspersus selected microhabitats with high coverage of filamentous algae at settlement, but among-reef variability in filamentous algae did not predict large-scale patterns of recruitment (Levin et al 1997). The inability to scale-up may occur because of low variability of the preferred substratum (Tolimieri 1995) or because the habitat signal may be scale-dependent (Syms 1995, Syms & Jones 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, large-scale patterns of fish abundance often correlate with habitat characteristics of reefs (e.g. Levin et al 1997). While the literature is replete with studies of fish-habitat associations, most of these studies are conducted at a single spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…We coded habitat characteristics into 2 functional groups, structure (filamentous and fleshy algae types) and non-structure (sand, gravel, and crustose algae), because these characteristics of the habitat are known to be important for recruitment in cunner (Levin 1991, Levin et al 1997). We define 'gravel' as rocks less then 5 cm in diameter with no algal cover.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to note that after settlement an overall decrease in recruit abundance at a reef was assumed to be mortality since cunner recruits possess very limited movement (Tupper & Boutilier 1995a, 1997. Numerous studies have found that differences in macroalgae type and structure are essential determinants of recruitment in temperate reef fish species (Jones 1984, Carr 1989, Connell & Jones 1991, Levin 1991, 1994b, Levin et al 1997. For example, structural quality of habitat is known to be an important determinant of post-settlement recruit abundance in cunner (Levin 1993, 1994b, Tupper & Boutilier 1995a.…”
Section: Habitatmentioning
confidence: 99%
“…One of the primary bases for understanding fish assemblages is the knowledge of their distribution and abundance and their relationship with abiotic factors (Inoue et al, 2008), as well as factors that will limit or affect a change in population (Levin et al, 1997). Several studies from different regions have emphasized abiotic factors, such as temperature and salinity (Harrison & Whitfield, 2006), salinity and turbidity (Cyrus & Blaber, 1992;Barletta et al, 2005), turbidity (Cyrus & Blaber, 1987;Abou-Seedo et al, 1990), morphodynamic models (Inui et al, 2010), and input of freshwater and river flow (Barletta et al, 2005;Vinagre et al, 2009;Baptista et al, 2010;Castillo-Rivera, 2013) as factors that influence the abundance of young fish in these shallow water habitats.…”
Section: Introductionmentioning
confidence: 99%